Effect of dietary lysine on performance and expression of electron transport chain genes in the pectoralis major muscle of broilers. (21st October 2016) - Brito, C. O.; Dutra, J. L. L.; Dias, T. N.; Barbosa, L. T.; Nascimento, C. S.; Pinto, A. P. G.; Albino, L. F. T.; Fernandes, R. P. M.; Macário, M. S.; Melo, J. S.
Abstract : The aim of this study was to evaluate the effect of dietary lysine on performance, protein deposition and respiratory chain gene expression in male broilers. A total of 252 Cobb 500 broilers were distributed, in a completely randomized design, into four treatments with seven replicates of nine birds per experimental unit. Experimental treatments consisted of diets based on corn and soybean meal, with four levels of digestible lysine: 1.016%, 1.099%, 1.182% and 1.265%. The increase in the level of digestible lysine in the diet provided higher weight gains, feed efficiency and body protein deposition. Birds fed the lowest level of dietary lysine (1.016%) showed a lower expression of genes such as NADH dehydrogenase subunit I ( ND1 ), cytochrome b ( CYTB ) and cytochrome c oxidase subunits I ( COX I ), II ( COX II ) and III ( COX III ), displaying the worst performance and body protein deposition. This demonstrates the relationship existing between the expression of the evaluated genes and the performance responses. In conclusion, results indicate that broilers fed diets with higher levels of digestible lysine have increased messenger RNA expression of some genes coded in the mitochondrial electron transport chain ( ND1, CYTB, COX I, COX II and COX III ). It may be stated that diets with proper levels of digestible lysine, within the 'ideal protein' concept, promote the expression of genes, which increases the mitochondrial energy, thereby fostering body protein deposition and the performance of broilers in the starter phase.